2013
DOI: 10.1108/jhom-10-2012-0207
|View full text |Cite
|
Sign up to set email alerts
|

A model of organisational dysfunction in the NHS

Abstract: A model has been developed to increase understanding of dysfunctional organisational behaviour in the NHS primarily for leaders/managers of health services, health service regulators and health researchers/academics. Research, with ethical approval, is currently being undertaken to test and develop the conceptual model to further reflect the complexities of the NHS culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…We are capturing another dynamic of 'organisational/institutional bullying' that operates at the organisational/institutional level and should not be explained away by blaming rogue individual managers. 160,161 This does not wholly capture the dynamic we observed. Part of the explanation may reside with the advent of new managerialism exercised within the NHS, 162 which emphasises organisational control, a centralised hierarchy and performance.…”
Section: Institutional Controlmentioning
confidence: 81%
“…We are capturing another dynamic of 'organisational/institutional bullying' that operates at the organisational/institutional level and should not be explained away by blaming rogue individual managers. 160,161 This does not wholly capture the dynamic we observed. Part of the explanation may reside with the advent of new managerialism exercised within the NHS, 162 which emphasises organisational control, a centralised hierarchy and performance.…”
Section: Institutional Controlmentioning
confidence: 81%
“…In the proposed model of organisational dysfunction (Pope and Burnes 2013), the three concepts of organisational silence, normalised corruption and protection of image reflect three aspects and perspectives of the NHS culture. The mechanisms of selective moral disengagement enable the persistence of this dysfunctional culture.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Negative Behaviour in the NHS In Pope and Burnes (2013), an extensive literature review was detailed on the topic of negative behaviour within the NHS. The review identified some key themes as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations